Thermodynamics of non-Newtonian fluids (drilling mud) - Beletsky Jа.S.; Shymko, T.J.; Beletsky, I.J.; Senyushkovych, M.V. (Physics and Chemistry of Solid State, 2016)
Using the method of pressure balance with balance energy forms, calculations are made hidrotermodynamichni mobile hydraulic flow in the well drilling fluids, water-based, which accumulate and transmit energy to other elements. The cases of the flow of liquid upwards (against gravity) and the current flow under gravity down to the bottom hole. The resulting complex equation with specific values ​​that do not depend on the scale of thermodynamics and fluid mechanics processes that occur in the borehole. By combining different similarity criteria can assess the impact of these processes on the performance of any operation in the well during its construction. The dependences can be used dlyautochnennya procedures governing the calculation of regime and technological parameters of the construction of deep wells.